High fidelity [videorecording (Blu-Ray)] - DeVincentis, D. V.; Pink, Steve; Cusack, John, 1966-; Cusack, John, 1966-; Rosenberg, Scott, 1963-; Black, Jack, 1969-; Bonet, Lisa, 1967-; Carter, Joelle; Cusack, Joan, 1962-; Gilbert, Sara, 1975-; Hjejle, Iben, 1971-; Louiso, Todd; et al. (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2012)
Rob Gordon's semi-failing record store isn't the only thing in his life that's floundering. When his longtime girlfriend walks out on him, Rob's needle skips the love groove, and he is forced to examine his past romantic failures in his own unique way.